LANDSCAPES, SETTLEMENTS AND TRADITIONAL HOUSING IN SAMTSKHE-JAVAKHETI, GEORGIA - Maisuradze, Roman; Khardziani, Tamar; Eradze, Tea (Quaestiones Geographicae, 2021)
A change in livelihood and folk architecture is an indicator of cultural landscape transformation, which is often the result of changes occurring in the natural and socio-political realms. The diversity of architectural types of buildings as an element of landscape diversity distinguishes our research region. The presented study deals with a long-term change of housing and architectural types of settlements. Our goal was to identify, geolocalise, and classify the vernacular architecture of Samtskhe-Javakheti within the different types of natural landscapes. For this purpose, we used the HGIS (Historical Geoinformation System) approach, which comprises the application of both historic sources and GIS technologies. We identified seven types of buildings in the study area, the characteristics of which depended on the natural landscape features. The following factors had been determining the geography of the construction: geology, seismicity, terrain, climate, access to building materials and defence. Dominant architectural types of buildings in the study region were as follows: fortress Rabat with stone houses, stone houses, semi-underground houses mixed with stone houses, semi-underground houses, terraced semi-underground houses, cave dwellings and wooden log houses. In modern times, it is quite rare to come across these kinds of architectural buildings, and there is a tendency of their disappearance.